Platelet rich fibrin and commercial sealants for dural closure in neurosurgery: An in vitro study - Katerina Argiti; Mukesch J. Shah; Kevin Joseph; Vidhya M. Ravi; Angeliki Stathi; Florian Volz; Amir El Rahal; Daniel Strahnen; Jürgen Grauvogel; Roland Rölz; Ulrich Hubbe; Jürgen Beck; et al. (PLoS ONE, 2025)
Background Watertight closure of the dura mater is essential after neurosurgical interventions to avoid complications such meningitis, intracranial hypotension and surgical site infections. In addition to conventional suturing techniques, various biomaterials have been proposed as sealants to minimize the risk of leakage. We previously reported that patient derived platelet-rich fibrin (PRF), an autologous biomaterial, significantly improves watertight dural closure when applied as an onlay over a standard running suture. To demonstrate the efficacy of this method, we aimed to compare this orthobiological approach with other commercially available sealants. Methods We utilized an in vitro testing device that allowed for the assessment of watertight dura mater closure via hydrostatic testing. On our testing phantom using freshly harvested bovine dura maters, a standardized 20-mm incision was closed using a running suture, and the leak pressure was measured initially without (primary leak pressure) and subsequently with on lay augmentation (secondary leak pressure) using either PRF, fibrinogen- and thrombin-coated collagen patch (TachoSil®), collagen matrix graft (DuraGen®), Polyethylenglykol (PEG) and polyethylene glycol ester and trilysine amine hydrogel solution (DuraSeal®), polyethylene glycol, protein-reactive polyethylene glycol monomer coated collagen matrix (Hemopatch®) or polyethylenimine component autospray sealant (Adherus®). Results The outcomes demonstrate that the usage of a dural onlay in addition to the standard running suture exhibited a substantial improvement in leak pressure compared to the running suture alone. Specifically, the median leak pressure was improved by 3.5 times, where the combined approach was able to withstand 38 cm H2O, whereas the running suture alone had a median leak pressure of 11 cm H2O. Upon evaluating the performance of the sealants, we identified two categories of dural sealants: a medium performance group (30 ± 2 cm H2O) comprised of Adherus® (31 cm H2O), DuraGen® (31 cm H2O), and Hemopatch® (28 cm H2O), and a high-performance group composed of DuraSeal® (45.5 cm H2O), and TachoSil® (41 cm H2O). Patient-derived PRF was able to withstand a max pressure of 45 cm H2O, falling into the high-performance group. Of all the sealants tested in this study, the PRF based patch demonstrated the lowest variance in leak pressure among all the tested sealants. Conclusions Autologous platelet-rich fibrin in a two-step procedure displayed enhanced augmentation and reinforced watertight closure of the dura mater, exhibiting a four-fold increase in leak pressure compared to standard running suture alone. Among other commonly utilized commercial sealants, it ranked second with demonstrated consistency in its performance.